Teacher’s Perception On Online Learning During Covid-19 At Smkn 5 Vocational School Bandung - et. al., Alvii T.B. Siregar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Adaptation to the COVID-19 Pandemic includes online learning, with no exception to vocational schools such as SMKN 5 Bandung. With more courses being dependent on practical than theory work, teachers and students need extra effort to deliver and understand the materials and practice leaning on kinesthetic, auditory, and visual stimulations. Thus, it has become a challenge for the effectiveness of learning via the internet. The research explores teachers' perceptions at SMKN 5 Bandung regarding online learning. It employed the quantitative descriptive method to analyze and arrive at a conclusion based on the online questionnaire 58 teachers as respondents completed. The results showed that they had used various applications/platforms such as Google Classroom, but they need more information on suitable platforms and content. It is recommended that they receive effective platform and content training to face limitations, especially audio-visual delivery.